PELATIHAN KADER MENINGKATKAN KEMAMPUAN KEBERLANJUTAN MENYUSUI DAN PERAWATAN METODE KANGURU DI RUMAH - Muladefi Choiriyah; Annisa Wuri Kartika; Niko Dima Kristianingrum; Endah Panca Lydia Fatma; Ridhoyanti Hidayah (Viva Medika, 2017)
WHO recommendation to continue low birth weight (LBW) baby management at home were breastfeeding and kangaroo mother care (KMC). However, the implementation of them less than optimal. Mother’s experience in conducted breastfeeding and PMK at home would be difficult due to physical and emotional change during postpartum, newborn health and physical condition, lack of support, and tradition that inhibit exclusive breastfeeding. So that cadre’s role as breastfeeding support group needed by them. The aim of this study to analyze cadre’s competence about continuing breastfeeding and KMC at home by cadre’s training. This quasi experimental study conducted on Kelurahan Kotalama area in Malang, on January 2017. Cadre who involved in this study were toddler’s cadre who had permanent resident in Kelurahan Kotalama area, never had breastfeeding and KMC training, and active as toddle cadre in at least 6-month period. Cadre’s competence assessed through their knowledge, attitude, and skill toward continuing breastfeeding and KMC. The data collection by breastfeeding and KMC questioner to assess cadre’s knowledge and attitude. Cadre’s skill assessed by observation in Posyandu next month. The result of this study shown that there were enhancement of cadre’s knowledge, attitude, and skill towards continuing breastfeeding and PMK which statistically significant (p-value 0,000 and 0,031) and they were able to teach breastfeeding and KMC properly in their communities. The conclusions were cadre’s training enhance cadre’s competence towards continuing breastfeeding and KMC at home. Keywords: Cadre’s training, Breastfeeding, Kangaroo Mother Care, low Birth Weight.